Readiness and Challenges of the Construction Industry in Implementing Building Information Modelling (BIM) - Mohd Saf'a, Miza Raimi; Tze Kiong, Tee; Abd Nasir, Nuraliah (Journal of Technical Education and Training, 2023)
Building Information Modelling (BIM) is one of the innovative approaches that has been developed and widely accepted in the construction industry. In Malaysia, BIM usage is still low and not many firms have taken full advantage of its potential despite the investment in BIM being proven to be well worth the cost of implementation to organizations. Therefore, this study has been conducted to identify the current status of BIM implementation in Malaysia. This study uses a qualitative approach with an explanatory research design to explore the phenomenon of BIM implementation in the construction industry. This study was aimed to identify the readiness and challenges in BIM implementation from twelve (12) participants from consultants and contractors in Malaysia who have already implemented and not have implemented BIM where the researcher used purposive sampling technique with snowballing sampling. In obtaining the data from participants, the researcher has conducted a semi-structured interview data collection technique. The data were then analyzed using thematic analysis to identify patterns and themes among the research questions in two categories of participants. This study finds that the rate of BIM implementation in construction industry is very low and the most factors influence companies’ readiness in BIM implementation from both categories of participants are client, enforcement from authority and lack of project that needs BIM. This study also found that the most challenges faced in BIM implementation are BIM exposure, cost implementation and others. In addition to that, this study proposing effective strategies for enhancing the BIM implementation in Malaysia such as introducing of BIM in university curriculum, BIM enforcement from the authority and others.